DIODE-LASER AND FOURIER-TRANSFORM SPECTROSCOPY OF THE (CH3OH)-C-13 C-O STRETCHING MODE - Pereira, D.; Cruz, F. C.; Moraes, João Carlos Silos [UNESP]; Scalabrin, A. (Plenum Publ Corp, 1994)
In this work we present high resolution Doppler limited absorption spectra measurements of the C-O stretching mode of (CH3OH)-C-13, obtained from diode laser spectroscopy, and the Fourier Transform spectrum obtained at 0. 12 cm-1 resolution. By using these data and previously known spectroscopic information, we determined the frequency and the J quantum number for the multiplets of the P and R(J) branches of the C-O stretching fundamental band. Infrared transitions in coincidence with emission lines of the regular CO2 laser and some of its isotope parents are pointed out.